Dimensi Keberagamaan Ngestu dalam Upacara Ngaben - I Made Pasek Subawa (Sphatika: Jurnal Teologi, 2020)
Implementation ngestu the cremation ceremony is one effort that was built in the tradition of the community to be able to unite ourselves on the social status, class, social stratification, and social attributes in the social life of the religious. In its implementation uphold a sense of solidarity and togetherness to build egalitarian values ​​for all citizens with the same service. But the objective reality and historical indicate that the Balinese social structure divided into traditional classes where each class has a class solidarity, prestige, and attributes that can be used as a class identity. All of the attributes relating to the status inherent in a person and has important implications on the establishment of a hierarchy of social and previledge which refers to the position of high-low as well as superior and inferior in leader ship of the network system, where the higher grade is considered to have power and authority over spacious with others in the social and religious life in the community. The difference can be deconstructed with realistic thinking with reference to the literature, ie essentially every human being is the same, because it comes from God. Therefore, there is no human reason to distinguish itself with other human beings, because of the social realities on the social attributes of a product of human culture as a result of erroneous interpretation of the teachings of the holy book of the Vedas.